Adsorption material, preparation method thereof and method for removing cesium ions

By using the combination of Prussian blue analog and hydrophilic resin in the adsorption material, the adsorption performance of cesium ions is optimized, and the problems of insufficient saturation adsorption capacity and long adsorption equilibrium time of existing adsorption materials are solved, thereby achieving efficient cesium ions Removal effect.

CN119215864APending Publication Date: 2024-12-31CHINA INSTITUTE OF ATOMIC ENERGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411441218.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing adsorption materials have insufficient saturation adsorption capacity and a long adsorption equilibrium time during the removal of cesium Cs, which affects the treatment efficiency of nuclear waste liquid.

Method used

Using Prussian blue analogs dispersed in hydrophilic resins as adsorption materials, the insoluble substance formed by reacting transition metal salts with hexacyanoferrous and hexacyanocobaltate is optimized to improve cesium ions The adsorption performance and combined with polyimide and polyacrylonitrile as resin frameworks form an adsorption material with improved adsorption capacity and adsorption equilibrium time.

Benefits of technology

The saturation adsorption capacity and adsorption equilibrium time of adsorbent materials are significantly improved, the removal efficiency of cesium ions is improved, the treatment cost is reduced, and mechanical and irradiation stability is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215864A_ABST
    Figure CN119215864A_ABST
Patent Text Reader

Abstract

The invention provides an adsorption material, a preparation method thereof and a method for removing cesium ions. The adsorption material comprises a Prussian blue analogue dispersed in hydrophilic resin, the Prussian blue analogue is an insoluble substance formed by enabling transition metal salt to react with hexacyanoferrate and hexacyanocobaltate in a solution, and the molar ratio of the hexacyanoferrate to the hexacyanocobaltate is (0.5-3): 1. The adsorbent material disclosed by the invention has improved saturation adsorption capacity and adsorption equilibrium time in cesium removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of radioactive waste liquid treatment, and in particular to an adsorption material, a preparation method thereof, and a method for removing cesium ions. Background Art

[0002] As a low-carbon and clean energy, nuclear energy is regarded by many countries as the preferred way to solve the problem of energy shortage. As of September 2023, my country has a total of 55 operating nuclear power units with a total installed capacity of 25.55 million kilowatts, ranking first in the world. In the nuclear fuel cycle, radioactive wastewater with varying degrees of contamination will be generated in every link of the entire process from uranium mining, smelting, fuel element production and manufacturing, application and spent fuel reprocessing. In the primary loop of nuclear facility operation and the reprocessing of spent fuel, a large amount of waste liquid containing radioactive cesium (Cs) isotopes will be generated, including 137 Cs and 134 Cs has a medium to long half-life, causing long-term internal radiation in the human body, which seriously endangers human health and needs to be removed.

[0003] In the related technologies, adsorption is one of the main methods for removing cesium Cs, but the existing adsorption materials still have obvious deficiencies in terms of equilibrium time, adsorption capacity, etc.

[0004] Therefore, it is necessary to provide an improved adsorption material. Summary of the invention

[0005] In view of this, the main object of the present disclosure is to provide an adsorbent material, a preparation method thereof, and a method for removing cesium ions. The adsorbent material has improved saturated adsorption capacity and adsorption equilibrium time in cesium removal.

[0006] The first aspect of the present disclosure provides an adsorbent material. The adsorbent material includes a Prussian blue analog dispersed in a hydrophilic resin, wherein the Prussian blue analog is an insoluble substance formed by reacting a transition metal salt with hexacyanoferrite and hexacyanocobaltate in a solution, and the molar ratio of the hexacyanoferrite to the hexacyanocobaltate is (0.5-3):1. The adsorbent material has improved saturated adsorption capacity and adsorption equilibrium time in cesium removal.

[0007] In some embodiments, in the solution, the ratio of the molar number of the transition metal salt to the sum of the molar numbers of the hexacyanoferrite and the hexacyanocobalamate is (0.5-1.5): 1. This is beneficial to optimize the structure of the Prussian blue analogue, thereby improving its adsorption performance for cesium ions.

[0008] In some embodiments, the hydrophilic resin includes polyimide and / or polyacrylonitrile. This is conducive to increasing the adsorption capacity of the adsorbent material and improving mechanical and radiation stability. Preferably, the hydrophilic resin is composed of polyimide and polyacrylonitrile; more preferably, the mass ratio of the polyimide to the polyacrylonitrile is (10-1):1; more preferably, the polyimide is obtained by polymerization of aromatic dibasic acid anhydride and aromatic diamine.

[0009] In some embodiments, the molar ratio of the hexacyanoferrite to the hexacyanocobalamate is (0.8-1.5):1.

[0010] In some embodiments, the transition metal of the transition metal salt is selected from one or more of nickel, cobalt, zinc, copper, vanadium, chromium, and titanium. The above transition metals are more conducive to the Prussian blue analogue having an optimized structure and improved adsorption performance for cesium ions. Preferably, the transition metal is selected from one or more of nickel, cobalt, and zinc. Preferably, the transition metal salt is selected from one or more of the nitrate, hydrochloride, and sulfate of the transition metal.

[0011] In some embodiments, the mass percentage of the Prussian blue analogue is 5% to 60% relative to the mass of the adsorbent material. This is more conducive to coordinating the effects of the inorganic material and the hydrophilic resin in the adsorbent material and improving its adsorption performance for cesium ions. Preferably, the mass percentage of the Prussian blue analogue is 35% to 45%.

[0012] The second aspect of the present disclosure provides a method for preparing the above-mentioned adsorption material, comprising the following steps:

[0013] S1, adding a transition metal salt solution to a solution of hexacyanoferrite and hexacyanocobalamate to form a precipitate to obtain a Prussian blue analog;

[0014] S2, forming a slurry including a hydrophilic resin, an organic solvent and the Prussian blue analog; and

[0015] S3, removing the organic solvent in the slurry to obtain the adsorption material.

[0016] The above method can prepare an adsorbent material having improved saturated adsorption capacity and adsorption equilibrium time in cesium removal in a simple and low-cost manner.

[0017] In some embodiments, in S1, the sum of the concentrations of hexacyanoferrite and hexacyanocobaltate in the solution of hexacyanoferrite and hexacyanocobaltate is 0.005 mol / L to 0.05 mol / L, which is beneficial to increase the adsorption sites in the prepared Prussian blue analog.

[0018] In some embodiments, in S1, the concentration of the transition metal salt solution is 0.010 mol / L to 0.025 mol / L, which is beneficial to increase the adsorption sites in the Prussian blue analog.

[0019] In some embodiments, in S2, the solvent of the organic solution is one or a mixture of dimethylformamide, dimethyl sulfoxide, and dimethylacetamide, which is conducive to uniform mixing of the Prussian blue analog and the hydrophilic resin.

[0020] In some embodiments, in S2, the concentration of the hydrophilic resin in the slurry is 0.005 g / mL to 0.050 g / mL, which is conducive to uniform mixing of the Prussian blue analog and the hydrophilic resin.

[0021] The third aspect of the present disclosure provides a method for removing cesium ions from nuclear waste liquid, wherein the cesium ions in the nuclear waste liquid are adsorbed using the adsorbent material provided by the first aspect or the adsorbent material prepared by the method provided by the second aspect, and the adsorbent material adsorbing the cesium ions is removed.

[0022] The present invention utilizes a Prussian blue analogue formed by the reaction of a transition metal salt solution with a solution of hexacyanoferrite and hexacyanocobalamate, and combines a hydrophilic resin as a framework to load the Prussian blue analogue, thereby providing a spatial structure that is conducive to the passage and exchange of ions, improving the saturated adsorption capacity, and shortening the adsorption equilibrium time.

[0023] In addition to the technical problems solved by the present disclosure, the technical features that constitute the technical solutions, and the beneficial effects brought about by the technical features of the technical solutions described above, other technical problems that can be solved by the present disclosure, other technical features included in the technical solutions, and the beneficial effects brought about by these technical features will be further described in detail in the following specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a relationship diagram between the adsorption capacity and adsorption time of cesium ions by the adsorbent material of Example 1 of the present disclosure.

[0026] Figure 2 Graph showing the relationship between the saturated adsorption capacity of the adsorbent material of Example 1 of the present disclosure for cesium ions and the pH of the solution. DETAILED DESCRIPTION

[0027] The technical solution of the present disclosure will be clearly and completely described below in conjunction with specific implementations and drawings. Obviously, the described implementations are only part of the implementations of the present disclosure, not all of the implementations. Based on the implementations in the present disclosure, all other implementations obtained by ordinary technicians in the field without creative work are within the scope of protection of this application.

[0028] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. In the event of a conflict, this specification takes precedence.

[0029] It should be noted that in the present disclosure, the term "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that a method or device including a series of elements includes not only the elements explicitly stated, but also other elements not explicitly listed, or also includes elements inherent to the implementation of the method or device. In the absence of further restrictions, an element defined by the sentence "comprising..." does not exclude the presence of other related elements in the method or device including the element.

[0030] Note that the phrase "and / or" when used in a list is meant to include alternative embodiments, including each individual component in the list and any combination of components. For example, the list "A, B, and / or C" is meant to include seven independent embodiments, including A, or B, or C, or A+B, or A+C, or B+C, or A+B+C.

[0031] The above steps are divided only for clear description. When implemented, they can be combined into one step or some steps can be split and decomposed into multiple steps. As long as they include the same logical relationship, they are all within the protection scope of this patent.

[0032] Definition of terms

[0033] As used herein, the term "Prussian blue analogs" (PBAs) refers to a class of three-dimensional open framework structures, which are composed of octahedral [M'(CN)6] bridged by transition metal ions. n- Examples of PBAs include, but are not limited to, KFe[Fe(CN)6], K 0.05 Fe 2.94 [Co(CN)6]2, K 0.62 Fe 0.70 Zn 1.82 [Co(CN)6]2, K 1.48 Zn2.26 [Co(CN)6]2, etc. For example, KFe[Fe(CN)6] is a three-dimensional open framework structure formed by iron ions bridging hexacyanoferrate ions. 0.05 Fe 2.94 [Co(CN)6]2 is a three-dimensional open framework structure formed by ferrous ions bridging hexacyanocobaltate ions.

[0034] As used herein, the term "hydrophilic resin" refers to a polymer having repeating monomer units with a ratio of (oxygen + nitrogen) to the total number of non-hydrogen atoms greater than or equal to 0.2.

[0035] As used herein, the term "hexacyanoferrate ion" refers to a ferrous ion of the formula [Fe(CN)6] 4- The anions shown.

[0036] As used herein, the term "hexacyanocobaltate ion" refers to a cation of the formula [Co(CN)6] 3- The anions shown.

[0037] The nuclear industry produces a large amount of waste liquid containing radioactive cesium (Cs) isotopes. There have been reports on the use of Prussian blue analogs to achieve the selective adsorption of Cs ions in water. This is based on the fact that the size of the lattice pores of Prussian blue is similar to the radius of hydrated Cs ions. However, the adsorption capacity of the adsorbent material in the related technology for cesium removal is less than 200 mg / g, the equilibrium time is long, the residual Cs ion concentration after adsorption is still relatively high, and the adsorption capacity is greatly affected by pH.

[0038] Based on this, the present application provides an adsorption material, a preparation method thereof, and a method for removing cesium ions. The present application and optional implementation methods are described in more detail below.

[0039] Adsorption material

[0040] The first aspect of the present application provides an adsorbent material. The adsorbent material includes a Prussian blue analog dispersed in a hydrophilic resin, wherein the Prussian blue analog is an insoluble substance formed by reacting a transition metal salt with hexacyanoferrite and hexacyanocobaltate in a solution, and the molar ratio of the hexacyanoferrite to the hexacyanocobaltate is (0.5-3):1.

[0041] Compared to the Prussian blue analogs formed by the reaction of a transition metal salt solution with a hexacyanoferrate solution or a hexacyanocobaltate solution alone, the Prussian blue analogs disclosed herein can provide improved saturated adsorption capacity and shortened adsorption equilibrium time. The hydrophilic resin disclosed herein is used as a skeleton to load the above-mentioned Prussian blue analogs, providing a structure with good mechanical strength that is conducive to the passage and exchange of ions. By combining the above-mentioned Prussian blue analogs and the hydrophilic resin, the adsorbent material disclosed herein can further improve the saturated adsorption capacity and shorten the adsorption equilibrium time when performing ion exchange with cesium.

[0042] Exemplarily, the molar ratio of the hexacyanoferrite to the hexacyanocobaltate is 0.5:1, 0.8:1, 1.0:1, 1.5:1, 1.8:1, 2.0:1, 2.5:1, 3.0:1 or a value within a range consisting of any two values. Optionally, the molar ratio of the hexacyanoferrite to the hexacyanocobaltate is (0.8-1.5):1.

[0043] The molar ratio of hexacyanoferrite and hexacyanocobalamate mentioned in the present application can be measured by instruments and methods known in the art. For example, the molar ratio can be measured by inductively coupled plasma atomic emission spectrometry (ICP-OES), and the instrument can be, for example, Thermo ICAP7400.

[0044] In some embodiments, in the solution, the ratio of the mole of the transition metal salt to the sum of the moles of the hexacyanoferrite and the hexacyanocobaltate is (0.5-1.5):1. This is beneficial to optimize the structure of the Prussian blue analog, thereby enhancing its adsorption performance for cesium ions. Exemplarily, the ratio of the mole of the transition metal salt to the sum of the moles of the hexacyanoferrite and the hexacyanocobaltate is 0.5:1, 0.8:1, 1.0:1, 1.2:1, 1.5:1 or a value within the range of any two values.

[0045] In some embodiments, the transition metal is selected from one or more of nickel, cobalt, zinc, copper, vanadium, chromium, and titanium. The above transition metals are more conducive to the Prussian blue analogue having an optimized structure and improved adsorption performance for cesium ions. Preferably, the transition metal is selected from one or more of nickel, cobalt, and zinc.

[0046] In some embodiments, the transition metal salt is selected from one or more of the nitrate, hydrochloride, and sulfate of the transition metal.

[0047] In some embodiments, the hydrophilic resin includes polyimide and / or polyacrylonitrile.

[0048] In some embodiments, the hydrophilic resin is composed of polyimide and polyacrylonitrile. The polyimide skeleton not only provides a spatial structure that is more conducive to ion passage, but also has radiation resistance and excellent mechanical properties, thereby facilitating improvement of the mechanical and radiation stability of the adsorbent material.

[0049] Alternatively, the polyimide can be polymerized from an aromatic dibasic acid anhydride and an aromatic diamine. Exemplarily, the aromatic dibasic acid anhydride can include at least one of pyromellitic acid anhydride (PMDA), 3,3',4,4'-diphenyl ether tetracarboxylic acid anhydride (ODPA), 3,3',4,4'-benzophenone tetracarboxylic acid anhydride (BTDA), bisphenol A diphenyl ether anhydride, 3,3',4,4'-biphenyl tetracarboxylic acid anhydride (BPDA), 2,3',4,4'-biphenyl tetracarboxylic acid anhydride, and 3,3',4,4'-biphenyl sulfone tetracarboxylic acid anhydride, but is not limited thereto. A preferred aromatic dibasic acid anhydride is pyromellitic acid anhydride. Exemplarily, the aromatic diamine may include at least one of p-phenylenediamine (PPD), m-phenylenediamine (MPD), 4,4'-diaminobiphenyl, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), diethyltoluenediamine (DETDA), 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) (MCDEA), and bis-sec-butylaminodiphenylmethane (MDBA), but is not limited thereto. A preferred aromatic diamine is p-phenylenediamine.

[0050] In addition to being able to serve as a skeleton to load the aforementioned Prussian blue analogs, polyacrylonitrile provides a structure with good mechanical strength that is conducive to the passage and exchange of ions. The nitrile group can also provide sites for coordination of metal ions to be adsorbed, which is beneficial to improving the adsorption capacity and adsorption rate.

[0051] In some embodiments, these two resins are used together as a support for the Prussian blue analog.

[0052] In some embodiments, the mass ratio of polyimide to polyacrylonitrile is (10-1):1. Exemplarily, the mass ratio of polyimide to polyacrylonitrile is 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1 or a value within a range consisting of any two values. Optionally, the mass ratio of polyimide to polyacrylonitrile is (8-4):1

[0053] In some embodiments, the mass percentage of the Prussian blue analogue is 5% to 60% relative to the mass of the adsorbent material. Thus, it is more conducive to coordinating the effects of the inorganic material and the hydrophilic resin in the adsorbent material disclosed herein, and improving the adsorption performance of cesium ions. Exemplarily, the mass percentage of the Prussian blue analogue is 5%, 10%, 20%, 30%, 35%, 40%, 45%, 50%, 60% or a value within the range of any two values ​​relative to the mass of the adsorbent material. Preferably, the mass percentage of the Prussian blue analogue is 35% to 45%.

[0054] Method for preparing adsorbent material

[0055] The embodiment of the present application also provides a method for preparing the adsorption material described in any of the above embodiments, comprising the following steps.

[0056] S1, a Prussian blue analogue is obtained by adding a transition metal salt solution to a solution of hexacyanoferrite and hexacyanocobalamate to form a precipitate.

[0057] S2, forming a slurry including a hydrophilic resin, an organic solvent and the Prussian blue analog.

[0058] S3, removing the organic solvent in the slurry to obtain the adsorption material.

[0059] The above method can prepare an adsorbent material having improved saturated adsorption capacity and adsorption equilibrium time in cesium removal in a simple and low-cost manner.

[0060] In some embodiments, the sum of the concentrations of hexacyanoferrite and hexacyanocobalamate in the solution of hexacyanoferrite and hexacyanocobalamate is 0.005 mol / L to 0.05 mol / L. For example, the sum of the above concentrations is 0.005 mol / L, 0.008 mol / L, 0.010 mol / L, 0.012 mol / L, 0.015 mol / L, 0.020 mol / L, 0.025 mol / L, 0.030 mol / L, 0.040 mol / L, 0.050 mol / L or a value within the range consisting of any two values.

[0061] In some embodiments, the concentration of the transition metal salt solution is 0.010 mol / L to 0.025 mol / L. Exemplarily, the concentration of the transition metal salt solution is 0.010 mol / L, 0.012 mol / L, 0.015 mol / L, 0.017 mol / L, 0.020 mol / L, 0.025 mol / L or a value within the range of any two values.

[0062] In some embodiments, the organic solvent is one or a mixture of dimethylformamide, dimethyl sulfoxide, and dimethylacetamide. This is conducive to uniform mixing of the Prussian blue analog and the hydrophilic resin. Preferably, the organic solvent is dimethylformamide.

[0063] In some embodiments, the concentration of the hydrophilic resin in the slurry is 0.005 g / mL to 0.050 g / mL. Exemplarily, the concentration of the hydrophilic resin in the slurry is 0.005 g / mL, 0.010 g / mL, 0.015 g / mL, 0.020 g / mL, 0.030 g / mL, 0.040 g / mL, 0.050 g / mL, or a value within a range consisting of any two values. This is conducive to uniform mixing of the Prussian blue analog and the hydrophilic resin.

[0064] Method for removing cesium ions

[0065] The embodiment of the present application also provides a method for removing cesium ions from nuclear waste liquid. The method uses an adsorbent material according to the present disclosure or an adsorbent material prepared according to the method of the present disclosure to adsorb cesium ions in the nuclear waste liquid and remove the adsorbent material adsorbing cesium ions. Therefore, the method has at least the same advantages as the adsorbent material. In addition to cesium ions, the nuclear waste liquid generally also includes radioactive ions such as strontium and cobalt. The adsorbent material of the present application exhibits good adsorption selectivity and radiation resistance.

[0066] The following is an explanation of the embodiments of the present application. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.

[0067] Example

[0068] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0069] The Cs ion content in the solution was analyzed using an ion chromatograph (Thermo Fisher Scientific, USA, model ICS1100).

[0070] Example 1

[0071] 1. Preparation of inorganic materials (i.e., Prussian blue analogs)

[0072] Prepare 5000mL of a mixed solution of K3Co(CN)6 and K4Fe(CN)6, where the concentrations of K3Co(CN)6 and K4Fe(CN)6 are both 0.010M. Prepare 5000mL of a 0.015M NiCl2 solution, and slowly drop 5000mL of the NiCl2 solution into the 5000mL mixed solution at below 10°C. After the addition is complete, continue stirring for 30 minutes, filter the precipitate, and wash it 3 times with deionized water. Vacuum dry overnight at 70°C to obtain 38g of inorganic material.

[0073] 2. Preparation of polyimide

[0074] Dissolve pyromellitic anhydride (21.8 g) and p-phenylenediamine (10.3 g) in a molar ratio of 1.05:1 in 500 mL of N,N'-dimethylformamide (DMF), stir at 10°C for 1 hour to obtain a polyamic acid solution. Add acetic anhydride (100 mL) and pyridine (20 mL) to the obtained polyamic acid solution, and stir the mixture at 80°C for 24 hours, then cool the obtained solution to room temperature and drip into distilled water in a beaker to form a polymer precipitate. Filter the precipitate and wash with methanol to obtain a polyimide.

[0075] 3. Preparation of hydrophilic resin solution

[0076] A 5000 mL solution of the above polyimide and polyacrylonitrile (commercially available reagents, number average molecular weight 10,000) in N,N-dimethylformamide (DMF) was prepared with a concentration of about 0.011 g / mL, wherein the mass ratio of polyimide to polyacrylonitrile was 5:1.

[0077] 4. Preparation of adsorption materials

[0078] The inorganic material is added to the hydrophilic resin solution in batches to obtain a slurry. Compared with the total mass of polyimide, polyacrylonitrile and inorganic material, the mass of inorganic material accounts for 40%. Stirring at room temperature for 5 hours to obtain a slurry, distilling under reduced pressure to remove the solvent in the slurry, washing the residue with deionized water 3 times, and vacuum drying at 60°C overnight to obtain an adsorbent material.

[0079] Example 2

[0080] The adsorption material was prepared in the same manner as in Example 1, except that the hydrophilic resin solution with a concentration of about 0.011 g / mL contained only polyimide.

[0081] Example 3

[0082] The adsorption material was prepared in the same manner as in Example 1, except that in the preparation of the inorganic material, the 0.015 M NiCl 2 solution was replaced by the 0.015 M ZnCl 2 solution.

[0083] Comparative Example 1

[0084] The adsorption material was prepared in the same manner as in Example 1, except that: in the preparation of the inorganic material, 5000 mL of an aqueous solution of K3Co(CN)6 was prepared with a concentration of 0.010 M; a 0.008 M NiCl2 solution was prepared, and 5000 mL of the NiCl2 solution was slowly added dropwise to 5000 mL of the mixed solution at a temperature below 10°C; after the addition was completed, stirring was continued for 30 min, the precipitate was filtered, and washed three times with deionized water; and vacuum dried at 70°C overnight to obtain 15 g of the inorganic material.

[0085] Comparative Example 2

[0086] The adsorption material was prepared in the same manner as in Comparative Example 1, except that in the preparation of the inorganic material, a 0.010 M aqueous solution of K4Fe(CN)6 was used instead of a 0.010 M aqueous solution of K3Co(CN)6 to obtain 14 g of inorganic material.

[0087] Comparative Example 3

[0088] The adsorbent material was prepared in the same manner as in Example 1, except that the hydrophilic resin solution was replaced with 5000 mL of a solution of low-density polyethylene (commercially available reagent, number average molecular weight 100,000) in toluene with a concentration of about 1 g / mL.

[0089] Performance Testing

[0090] 1. Adsorption equilibrium time and saturated adsorption capacity test

[0091] (1) Prepare 0.1 L of CsNO3 solution (initial concentration of Cs ions C0 = 30 mg / L), pH = 7.

[0092] (2) Take 5×10 -3 g of adsorbent material was put into the above solution and shaken at 25°C;

[0093] (3) At different times t, the residual Cs ion concentration C in the solution was tested using an ion chromatograph (Thermo Fisher Scientific, USA, model ICS1100). t , until the remaining Cs ion concentration remains basically unchanged, that is, the saturated adsorption concentration C e The time to reach this concentration is taken as the adsorption equilibrium time.

[0094]

[0095] The saturated adsorption capacities and adsorption equilibrium times of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0096] Adsorption capacity q at each time of Example 1 t The results are as follows Figure 1 As shown, it can be seen that the adsorption material of Example 1 reached saturated adsorption in 4 minutes.

[0097]

[0098] 2. Saturated adsorption capacity test of cesium ions at different pH

[0099] (1) Prepare 0.1 L of CsNO3 solution (initial concentration of Cs ion C0 = 20 mg / L), and adjust with 0.01 M nitric acid or 0.01 M sodium hydroxide to prepare solutions with pH values ​​of 2, 3, 4, 5, 6, 7, 8, and 9, respectively.

[0100] (2) Take 5×10 -3 g of the adsorbent of Example 1 was added to each of the above solutions, shaken at 25° C. for 15 minutes, and the adsorbent was removed by filtration.

[0101] (3) Use ion chromatography to test the Cs content in the adsorbed solution, and then calculate q e .

[0102] The test results are shown in the attached Figure 2 The adsorption material of Example 1 reaches saturated adsorption in 15 minutes within the pH range of 2 to 9, and the saturated adsorption capacity is basically not affected by pH.

[0103] 3. Deep cesium removal test

[0104] The cesium removal adsorbent materials of Examples 1-3 and Comparative Examples 1-3 were respectively loaded into a filter column with an inner diameter of 100 mm and a length of 800 mm. 137 Radioactive wastewater with a specific activity of Cs of about 1500 Bq / L was used as the influent and flowed through the glass column at a flow rate of 100 mL / min (6 BV / h), where BV refers to the filling volume of the cesium removal adsorbent material. 137 The variation of the specific activity of Cs with the effluent volume is shown in Table 1.

[0105] The test results of the adsorption materials prepared in the above Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.

[0106] Table 1

[0107]

[0108]

[0109] It can be seen from the above results that the adsorption material of the embodiments of the present disclosure has the advantages of increasing the saturated adsorption capacity and shortening the adsorption equilibrium time. 137 The specific activity of Cs is less than 120 Bq / L. In particular, the effluent of Example 1 137 The specific activity of Cs is less than 10Bq / L, achieving deep purification of wastewater.

[0110] Embodiment 4-5

[0111] In Example 4, the adsorption material is prepared in the same manner as in Example 1, except that when preparing a mixed solution of K3Co(CN)6 and K4Fe(CN)6, the concentrations of K3Co(CN)6 and K4Fe(CN)6 are 0.02M and 0.01M, respectively.

[0112] In Example 5, the adsorption material is prepared in the same manner as in Example 1, except that when preparing a mixed solution of K3Co(CN)6 and K4Fe(CN)6, the concentrations of K3Co(CN)6 and K4Fe(CN)6 are 0.01M and 0.02M, respectively.

[0113] The test results of the adsorption materials of Examples 1, 4 and 5 are shown in Table 2.

[0114] Table 2

[0115]

[0116]

[0117] It can be seen from the above results that when the molar ratio of hexacyanoferrite to hexacyanocobalamate in the PBAs of the inorganic materials of the embodiments of the present disclosure is within the above range, the inorganic materials have the advantages of increasing the saturated adsorption capacity and shortening the adsorption equilibrium time.

[0118] The above descriptions are only some specific embodiments of the present disclosure, which are intended to illustrate the present disclosure and are not intended to limit the scope of protection claimed in the present application. All modifications, substitutions, or direct / indirect applications made in other related technical fields based on the inventive concept of the present disclosure and using the description of the present application are included in the scope of protection claimed in the present application.

Claims

1. An adsorbent material comprising a Prussian blue analog dispersed in a hydrophilic resin, wherein: The Prussian blue analog is an insoluble substance formed by reacting a transition metal salt with hexacyanoferrite and hexacyanocobaltate in a solution, and the molar ratio of the hexacyanoferrite to the hexacyanocobaltate is (0.5-3):

1.

2. The adsorbent material according to claim 1, wherein In the solution, the ratio of the molar number of the transition metal salt to the sum of the molar numbers of the hexacyanoferrite and the hexacyanocobalamate is (0.5-1.5):

1.

3. According to the adsorption material according to claim 2, the hydrophilic resin comprises polyimide and / or polyacrylonitrile; preferably, the hydrophilic resin consists of polyimide and polyacrylonitrile; more preferably, the mass ratio of the polyimide to the polyacrylonitrile is (10-1):1; more preferably, the polyimide is obtained by polymerization of an aromatic dibasic acid anhydride and an aromatic diamine.

4. The adsorbent material according to any one of claims 1 to 3, wherein The molar ratio of the hexacyanoferrite to the hexacyanocobalamate is (0.8-1.5):

1.

5. The adsorbent material according to any one of claims 1 to 3, wherein The transition metal of the transition metal salt is selected from one or more of nickel, cobalt, zinc, copper, vanadium, chromium and titanium; preferably, the transition metal is selected from one or more of nickel, cobalt and zinc; preferably, the transition metal salt is selected from one or more of nitrates, hydrochlorides and sulfates of the transition metal.

6. The adsorbent material according to any one of claims 1 to 3, wherein Relative to the mass of the adsorption material, the mass percentage of the Prussian blue analogue is 5% to 60%; preferably, the mass percentage of the Prussian blue analogue is 35% to 45%.

7. A method for preparing an adsorption material according to any one of claims 1 to 6, comprising the following steps: S1, adding a transition metal salt solution to a solution of hexacyanoferrite and hexacyanocobalamate to form a precipitate to obtain a Prussian blue analog; S2, forming a slurry including a hydrophilic resin, an organic solvent and the Prussian blue analog; and S3, removing the organic solvent in the slurry to obtain the adsorption material.

8. The method according to claim 7, wherein: In S1, the sum of the concentrations of hexacyanoferrite and hexacyanocobaltate in the solution of hexacyanoferrite and hexacyanocobaltate is 0.005 mol / L to 0.05 mol / L; Preferably, in S1, the concentration of the transition metal salt solution is 0.010 mol / L to 0.025 mol / L.

9. The method according to claim 7, wherein: In S2, the solvent of the organic solution is one or a mixture of dimethylformamide, dimethyl sulfoxide, and dimethylacetamide; Preferably, in S2, the concentration of the hydrophilic resin in the slurry is 0.005 g / mL to 0.050 g / mL.

10. A method for removing cesium ions from nuclear waste liquid, comprising: The cesium ions in the nuclear waste liquid are adsorbed by the adsorbent material according to any one of claims 1 to 6 or the adsorbent material prepared by the method according to any one of claims 7 to 9, and the adsorbent material adsorbing the cesium ions is removed.

Citation Information

Cited By

  • Rubidium and cesium adsorbent as well as preparation method and application thereof

    CN121372304A